Restoration applications of resource objective wildfires in western US forests: a status of knowledge review - Huffman, David W.; Roccaforte, John Paul; Springer, Judith D.; Crouse, Joseph E. (Fire ecology, 2020)
Background Frequent-fire forests of the western United States have undergone remarkable changes in structure, composition, and function due to historical exclusion of naturally occurring fire. Mechanized tree thinning to reduce forest density and fuel loads tends to be expensive and cannot be effectively implemented across all lands, and there is increasing interest in managing naturally ignited wildfires for meeting forest restoration objectives. To investigate general effectiveness of resource objective (RO) wildfires for restoring frequent-fire and associated forests of the western United States, we conducted a review of the related peer-reviewed literature. Results Formal analysis of ecological responses to RO fires is relatively recent, and 21 of the 37 papers (57%) we reviewed were published between the years 2010 and 2018. We found 17 studies that investigated RO fire outcomes in Sierra Nevada forests, while other ecoregions that were represented in the literature included Arizona–New Mexico Mountains, Middle Rockies–Blue Mountains, and the Colorado Plateau. Yosemite National Park was utilized in 14 of the studies we reviewed. We noted several ecoregions where frequent-fire forests occur, but for which published studies on RO fires are lacking. The main focus of research (14 studies) was related to RO fire effects on forest structure, and next in importance was research (12 studies) related to fire severity, extent, and type, with studies of understory vegetation responses and landscape-scale patterns or dynamics also prevalent. Research findings indicated that RO fires were effective for reducing tree density and fire behavior; however, densities often remained above known historical ranges of variation in several studies. Understory responses reported in the literature were mixed with respect to effects on abundance and species richness. Increases in invasive species abundance in areas of high burn severity were consistently reported. Research on landscape patterns indicated that RO fires can increase heterogeneity with respect to vegetation distribution. Conclusion RO fires can be generally effective for restoration of frequent-fire forests, particularly on landscapes with long histories of fire use and in areas of moderate burn severity. More research is needed to test fire outcomes against specific restoration targets, and additional studies are needed concerning important ecological processes and functions.